Reclaiming the Nation : Muslim Women and the law in India - Narain, Vrinda, 1965- (Book collections on Project MUSE., 2008)
A timely account of the struggle for liberation within a restrictive religious framework, Reclaiming the Nation is an insightful look at gender, nationhood, and the power of self-determination.